The characteristic of neonatal hyperbilirubinemia before and after phototherapy at Sanglah Hospital, Denpasar, Bali in 2017 - Wayan Sulaksmana Sandhi Parwata; Putu Junara Putra; Made Kardana; Wayan Dharma Artana; Made Sukmawati (Intisari Sains Medis, 2019)
Background: Hyperbilirubinemia is the most clinical problem in newborn babies.  Hyperbilirubinemia occurs 60% in aterm babies and 80% in premature babies. This study aims to know the incidence of hyperbilirubinemia, characteristics of hyperbilirubinemia and effect of phototherapies to bilirubin levels.Methods: A cross-sectional retrospective study was conducted using medical records among 94 neonates with hyperbilirubinemia who treated with phototherapies at Sanglah hospital during 2017. Data regarding gender, gestational weeks, type of delivery, size for gestational age, the onset of hyperbilirubinemia, etiology, birth weight, maternal gravid status, and bilirubin levels were collected and analyzed using SPSS version 20 software descriptively.Results: From 94 neonatal hyperbilirubinemia that meet the inclusion criteria, 51 (54.3%)  males and 43 (45.7%) females based on gender. Mean gestational ages were 36.35±2.921 weeks. The major etiology of neonatal hyperbilirubinemia were breastfeeding jaundice 33 (25.8%), Prematurity 23 (18.7%), ABO incompatibility 13 (10.6%), Breast milk jaundice 11 (8.9%), gastrointestinal malformation 6 (4.9%), G6PD deficiency 5 (4.1%), and sepsis 3 (2.4%). The mean total bilirubin prior to phototherapy was 15.6±4.11 mg/dL whereas the indirect bilirubin was 14.56± 3.55 mg/dL. The duration of phototherapy in this study was 2.8±0.65 days.Conclusions: The incidence of neonatal hyperbilirubinemia during 2017 at Sanglah Hospital were predominantly caused by breastfeeding jaundice, prematurity, and ABO incompatibility. There were decreased bilirubin levels following phototherapies.